Satellite Fast Maneuver Control Technology Based on Parallel System - Youtao Gao; Jinghe Guo; Zhicheng You; Zezheng Dong; Yi Cheng (International Journal of Aerospace Engineering)
An on-orbit thrust estimation method of satellite based on parallel system, which can achieve high-efficiency and high-precision thrust estimation, is proposed. A complete satellite maneuvering parallel system framework is constructed. Initially, a real-time artificial model, which is consistent with the actual system, is established. The injection time of maneuvering control is estimated optimally based on the modification of the artificial model with the specific injection time treated as the optimization parameter. The jet time, with the minimum maneuvering error, is obtained. Then, a maneuver strategy is designed and fed back to the actual system. The method based on a parallel system with jet time as the optimal parameter has higher control accuracy than the previous maneuvering control, which only considers the speed increment. Simulation results show that the terminal error of the first maneuver using the parallel system method is less than 100 meters for a maneuvering mission of tens of kilometers.